Spatio-temporal evolution of ground motion intensity caused by reservoir-induced seismicity at the Pertusillo artificial lake (southern Italy) - Picozzi, Matteo; Serlenga, Vincenzo; Stabile, Tony Alfredo (Frontiers in Earth Science, 2022)
We investigate the spatiotemporal evolution of ground motion caused by reservoir-induced seismicity at the Pertusillo artificial lake in southern Italy. The area has a strong seismogenic potential, having been affected in the past by the 1857, Mw 7.0 Basilicata earthquake. We consider ~1000 microearthquakes occurred from 2001 to 2018 and recorded by a local network of 9 seismic stations. The ground motion intensity associated with microseismicity allows us to identify two periods, each lasting approximately two years. They are characterized by a high rate of events, but different source properties and spatial distribution. In the first period, the seismicity is spatially clustered close to the lake on faults with different orientation and kinematics. In the second period, the seismicity is distributed along the Monti della Maddalena faults. Comparing the ground motion intensity for the two periods, we observe that events for the first period are associated with higher stress levels than the others, in agreement with the b-values of the respective frequency-magnitude distributions. We compare the temporal evolution of the ground motion intensity with rainfall and water levels measured at the artificial lake, and the discharge of a ~80 km distant spring, which is strictly controlled by climate trends, and thus it provides information about regional processes acting on the southern Apennines. Our results show that the microseismicity is clearly associated with the Pertusillo artificial lake in the first period, while in the second period it can result from a combination of local effects due to the water table oscillations of the lake itself, regional tectonics, and the poroelastic and elastic phenomena associated with carbonate rocks hosting aquifers.